Translation priming in Malay-Arabic bilinguals - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmad H. Osman, Rahmah; Stevenson, Bruce; Ahmed, Mohamed Ayaaz; Jalaludin, Mohamad Afiudin; Mohd Kadri, Nursyuhaidah (Northeastern University, China, 2022)
It is argued that in the bilingual’s the first (L1) and second (L2) language, even proficient individuals rely on the information stored in the L1 lexicon. Thus, translation priming effects are found from L1-L2 but not necessarily from L2-L1. The valence of the word however could be encoded at an early stage of L2 acquisition and thus could have an effect onword activation and thus translation priming. The aim of this study is therefore to investigate translation priming in Malay-Arabic bilinguals and to investigate the effects of valence on these translations. A total of 68 participants with Malay as L1 and Arabic as L2, ranging from 19–24 years of age (M= 20.79 ± 1.51 years) were recruited. The priming paradigm was used in four language conditions L1–L1, L2–L2, L2–L1, and L1–L2.For each of the four language conditions, these reflect the factors, prime exposure (masked/overt), prime type (control, repetition and translation), and target valence (neutral, positive, negative). In L1-L2 conditions translation priming was found at a preconscious and conscious level when the target was neutral, positive or negative in valence. In the L2-L1 condition translation priming was only evident in positive and negative targets. In positive targets masked and overt priming effects were found, however for negative targets effects were only found when overt priming was used. This opens the door for further research in these phenomena.